Teachers’ and Parents’ Perceptions of Parental Involvement on Inner City Children’s Academic Success - Molly Zhou (Georgia Educational Researcher, 2014)
Parental involvement (PI) is an important factor in children’s academic learning. In this study, teachers’ and parents’ perceptions of parental involvement on inner city children’s academic success were examined. The setting of the study was in an inner city Tittle I elementary school with a 90% African American student population. A purposeful random sampling method was used in the study. Fifty five parents and 14 teachers participated in the study. The Parental Involvement Survey was used to collect data from the 69 participants. Collected data were analyzed with SPSS. The findings revealed that parents and teachers perceived that family, extended family, and community support were important for inner city children’s academic success. Teachers and Parents differed significantly on parental expectations, rewards, and educational decision making for the children. The paper discussed the implications of the research findings as well as suggestions for future research.